Analisis Implementasi Kebijakan Publik di Era Otonomi Daerah - Tri Wicaksono, Bagus; Hidayat, Wahyu; Muhammad Mughni Labib (Idarotuna : Journal of Administrative Science, 2025)
Regional autonomy grants broad powers to local governments to manage government affairs and implement public policies according to the needs of local communities. This study analyzes the implementation of public policies in the regional autonomy era by examining various factors influencing their success and obstacles. Through a qualitative approach, including literature review and policy document analysis, this study finds that public policy implementation in the regional autonomy era is influenced by human resource capacity, budget availability, inter-institutional coordination, and community participation. The results indicate that although regional autonomy provides flexibility in policymaking, various challenges remain in its implementation, such as capacity gaps between regions, fiscal constraints, and a lack of vertical and horizontal coordination.